Usability Analysis of Andalusian Spas’ Websites - Anaya-Aguilar, Rosa María; Gemar-Castillo, Germán; Anaya-Aguilar, Carmen (MDPI, 2021)
Health tourism is booming all over the world, and thermal spa tourism in Spain is a type of tourism aimed at integrating with nature, achieving sustainable development. In general, its facilities are located in areas specially protected by environmental legislation. This tourism sector attracts an increasingly wide market segment that has become more demanding and better informed and that more frequently uses the Internet to gather information. Tourists’ shopping and consumption habits are increasingly influenced by new information and communication technologies (ICTs), making these a topic of interest among academics and professionals. Website development has been shown to be an area of innovation for spa facilities, but evidence has also been found that this sector has experienced difficulty in adopting ICTs. This research sought to analyse spa websites’ usability by conducting an exploratory investigation of different websites’ contents. The results reveal that the use of new web technologies by spas is underdeveloped, although these facilities have achieved good positions in Internet search engines due to the synergistic effect of the official tourism websites. That is why most of them tell their story, detail their nature and the protection of their spaces. In this way, spas turn their websites into communication channels that convey to tourists their commitment to the environment and sustainable development.
Keywords: Viajes - Aspectos sanitarios; Andalusia; Spa; Website analysis; Tourism; Health; Environmental sustainability